Cell-mediated and serology-based tests for Mycobacterium ulcerans disease: A systematic review and meta-analysis. - Michael S Avumegah; Nilakshi T Waidyatillake; Wojtek P Michalski; Daniel P O'Brien; Tiffanie M Nelson; Eugene Athan (Public Library of Science (PLoS), 2020)
Buruli ulcer (BU) is a subcutaneous necrotic infection of the skin caused by Mycobacterium ulcerans. It is the third most common human mycobacterial disease after tuberculosis (TB) and leprosy. The available methods for detection of the bacilli in lesions are microscopic detection, isolation and cultivation of the bacterium, histopathology, and polymerase chain reaction (PCR). These methods, although approved by the World Health Organization (WHO), have infrastructural and resource challenges in medical centres and cell-mediated immunity (CMI) and/or serology-based tests have been suggested as easier and more appropriate for accurate assessment of the disease, especially in remote or underdeveloped areas. This study systematically reviewed and conducted a meta-analysis for all research aimed at developing cell-mediated immunity (CMI) and/or serology-based tests for M. ulcerans disease. Information for this review was searched through PubMed and Web of Science databases and identified up to June 2019. References from relevant articles and reports from the WHO Annual Meeting of the Global Buruli Ulcer Initiative were also used. Twelve studies beginning in 1952, that attempted to develop CMI and/or serology-based tests for the disease were identified. These studies addressed issues of specificity and sensitivity in context of antigen composition as well as study heterogeneity and bias. The two main types of antigenic preparations considered were pathogen-derived and recombinant protein preparations. There was slight difference in test performance when M. ulcerans recombinant proteins [positivity: 67.5%; 32.5%] or pathogen-derived [positivity: 76.0%; 24.0%] preparations were used as test antigens among BU patients. However, pathogen-derived preparations were better at differentiating between patients and control groups [odds ratio (OR) of 27.92, 95%CI: 5.05-154.28]. This was followed by tests with the recombinant proteins [OR = 1.23, 95%CI: 0.27-5.62]. Overall, study heterogeneity index, I2 was 92.4% (p = 0.000). It is apparent from this review that standardisation is needed in any future CMI and/or serology-based tests used for M. ulcerans disease.